Serology of paracoccidioidomycosis - I. Evaluation of the indirect immunofluorescent test - Mistreta, Tania; Souza, Maria Julia; Chamma, Luiz Gastão; Pinho, Sheila Zambello; Franco, Marcello (Springer Nature, 1985)
The purposes of the present work were: i) to study the positivity indices and compare titers obtained with the indirect immunofluorescence (II), tube precipitation (TP), complement fixation (CF) and double immunodiffusion on agar gel (ID) tests in the sera of 196 patients with paracoccidioidomycosis before treatment, and ii) to compare the initial titers of II with those obtained 1 year or more after treatment. II was the most sensitive serologic reaction (85.2%), and the positivity indices for CF, ID and TP were 67.7%, 66.0% and 50.0%, respectively. The sera tended to show parallel mean titers in II, CF and TP tests. One year after treatment there was a fall in titers of II in 66.2% of patients. The data, taken as a whole, demonstrate the usefulness of the indirect immunofluorescent test and the importance of using 2 or more serologic tests for the diagnosis and monitoring of patients with paracoccidioidomycosis. © 1985 Martinus Nijhoff/Dr W. Junk Publishers.
Keywords: blood and hemopoietic system; clinical article; complement fixation; diagnosis; fungus; human; human cell; immunodiffusion; immunofluorescence; methodology; precipitation test; south american blastomycosis; Antibodies, Fungal; Complement Fixation Tests; Fluorescent Antibody Technique; Fungi; Humans; Immunodiffusion; Paracoccidioides; Paracoccidioidomycosis; Precipitin Tests; Serologic Tests